FAKTOR PENENTU KETEPATAN PELAPORAN KEUANGAN PERUSAHAAN : PERUSAHAAN NON KEUANGAN DI INDONESIA TAHUN 2021-2023 - Windi Febriyanti Putri Inayah; Erma Setiawati (ITB AAS Indonesia Surakarta, 2025)
Financial reports are characterized by timeliness, which implies that the availability of information at the opportune moment influences decision-making processes. This study aims to investigate and analyze the impact of firm size, leverage, profitability, board independence, and audit quality on the timeliness of financial reporting. The population comprises all non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. A total of 269 companies were selected as samples using the purposive sampling technique. This study employs logistic regression analysis, yielding results that indicate audit quality significantly affects the timeliness of financial reporting. Conversely, firm size, leverage, profitability, and board independence do not exert a significant influence on the timeliness of financial reporting.